Samples designs for agricultural surveys by the maximum efficiency stratification. - Vicente, José Roberto; Camargo, Milton Nogueira de; Peres, Rubens Ferracioli (Pesquisa Agropecuaria Brasileira, 2014)
Samples are designed for data surveys of farm owners associated to the Cooperativa dos Agricultores da Região de Orlândia, Brazil, by the maximum efficiency stratification. The results were compared with the method of simple random sample and were considered adequate to the desired finality.